Abstract reasoning abilities of college students - Paras, Erlinda G. 1940-
The objectives of the study are the following: to determine the different levels of abstract reasoning among selected University of the East college students, to establish the relationship between levels of abstract reasoning and selected factors in the home and environment, and to relate the results of the study to the formulation of guidelines for more effective science teaching. Results of the study indicate that little vertical growth in abstract reasoning abilities occurs between the first and fourth year of college work. Likewise, the ability to make generalizations as measured by TAT is a function of degree program or specialized formal training but the cognitive level as measured by PCT is not.